The structure of worker compensation in Brazil, with a comparison to France and the United States - Naércio Aquino Menezes Filho; Marc-Andreas Mündler; Garey Ramey (Center for Economic Studies and ifo Institute (CESifo), 2006)
We employ a comprehensive matched employer-employee data set for Brazil to analyze wage determinants and compare results to Abowd, Kramarz, Margolis and Troske (2001) for French and U.S. manufacturing. Returns to education and experience in Brazilian manufacturing exceed those of the other countries, while occupation differentials are similar. The gender differential in Brazilian and U.S. manufacturing coincides, and is considerably smaller than in France. Estimates are unaffected by selectivity of Brazilian workers into formal employment. The links between firm performance and wage components in Brazil resemble those of France. Worker characteristics have comparable explanatory power for manufacturing wage variability in the three countries but establishment-fixed effects explain relatively less of the Brazilian wage variation. Despite the inclusion of establishment effects, regressors predict at most sixty percent of wage variability in any Brazilian sector, suggesting that explanations for earnings variability ought to focus on worker characteristics, not establishment wage policies.
Keywords: J31; D21; 330; wage structure; wage inequality; matched employer-employee data; formal and informal employment; selectivity; Brazil; Lohnstruktur; Industriearbeit; Lohndifferenzierung; Vergleich; Schätzung; Brasilien; USA; Frankreich